2019
DOI: 10.1002/brb3.1303
|View full text |Cite
|
Sign up to set email alerts
|

Mental fatigue assessment may add information after aneurysmal subarachnoid hemorrhage

Abstract: Background Mental fatigue, as part of cognitive dysfunction, has been reported to be common after subarachnoid hemorrhage and it significantly affects quality of life. Aims of the Study The aim of this study was to assess mental fatigue one year after an aneurysmal subarachnoid hemorrhage and to correlate the degree of mental fatigue to functional outcome assessed with the Extended Glasgow Outcome Scale (GOSE). Methods One year after an aneurysmal subarachnoid hemorrhage, the GOSE was assessed and a questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…The instrument used for measuring fatigue was, however, different as Buunk et al ( 2018 ) used The Dutch Multifactor Fatigue Scale. Sörbo et al ( 2019 ) investigated post-aSAH fatigue with the MFS questionnaire only and found 57% of patients scoring ≥10.5 points. They used no other questionnaires and their evaluation of physical fatigue was hence not beyond the means of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The instrument used for measuring fatigue was, however, different as Buunk et al ( 2018 ) used The Dutch Multifactor Fatigue Scale. Sörbo et al ( 2019 ) investigated post-aSAH fatigue with the MFS questionnaire only and found 57% of patients scoring ≥10.5 points. They used no other questionnaires and their evaluation of physical fatigue was hence not beyond the means of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Sörbo et al ( 2019 ) demonstrated a correlation between MFS score and functional outcome after aSAH as expressed with GOSE, where none of their fully recovered patients (GOSE 8) had an MFS sum score suggestive of mental fatigue (≥10.5). Presently, all five mRS 0 patients scored ≥4 on FSS and three of them scored ≥10.5 on MFS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, fatigue was a very common concern in our study, which is in accordance with other studies. [32][33][34] Rehabilitation in the first months after an aSAH often focuses on helping the patient manage their ADLs, return home and, if possible, return to work. Less attention has been paid to more diffuse, cognitive symptoms that may manifest later.…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue after aSAH has been described as prevailingly mental fatigue, 1,24 and therefore we also used the Mental Fatigue Scale (MFS). 25 It consists of 15 items that relate to fatigue, sleep patterns, and affective and cognitive symptoms.…”
Section: Methodsmentioning
confidence: 99%